PERANCANGAN SISTEM INFORMASI KETIDAKLENGKAPAN PENGISIAN CATATAN MEDIS (KLPCM) DI PUSKESMAS LINGGAR - Aufa Luthfiyati Aqilah; Abdul Wahab; Johni S. Pasaribu; Sali Setiatin (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The implementation of activities in the filing unit at the Linggar Health Center still has obstacles, namely the recording of loans and the return of medical record documents is still done manually, and the implementation of incompleteness checking the filling of mendis records that are still not carried out optimally. Difficulty when searching data when a missfile occurs can affect health services for patients. In order to support the implementation activities in the filing unit , a system is needed that is expected to facilitate the work of medical record officers. This research is qualitative with observational data collection techniques. This information system design method uses the System Development Life Cycle (SDLC) with a waterfall model. The results of this study are an application that can help the process of checking the incompleteness of filling out medical records in a computerized manner. The application is created with the PHP programming language with a codeigniter framework and the database used is MySQL.